PERBANDINGAN METODE ORDINARY LEAST SQUARE (OLS) DAN METODE REGRESI ROBUST PADA HASIL PRODUKSI PADI DI KABUPATEN INDRAMAYU - Prichilia Putu Makarti; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
One of the goals of SDGs (Sustainable Devloment Goals) on food security is to end hunger, achieve food security, improve nutrition and promote sustainable agriculture. So that food security is an important concern for the government, especially on rice commodities. In 2013 West Java became the largest producer of production in Indonesia and one district which became the largest rice producing center in West Java is Indramayu District with total production of 1,435,938 tons. OLS (Ordinary Least Square) is a regression method that minimizes the number of quadratic errors. While robust regression is a regression method used when the distribution of the error is not normal or the existence of the influence of the model. In this research, it is found that robust method is better than OLS method. Keywords: Rice, OLS, Robust